Allergy Enhances Neurogenesis and Modulates Microglial Activation in the Hippocampus - Klein, Barbara; Mrowetz, Heike; Thalhamer, Josef; Scheiblhofer, Sandra; Weiss, Richard; Aigner, Ludwig (Frontiers in Cellular Neuroscience, 2016)
Allergies and their characteristic TH2-polarized inflammatory reactions affect a substantial part of the population. Since there is increasing evidence that the immune system modulates plasticity and function of the central nervous system (CNS), we investigated the effects of allergic lung inflammation on the hippocampus – a region of cellular plasticity in the adult brain. The focus of the present study was on microglia, the resident immune cells of the CNS, and on hippocampal neurogenesis, i.e. the generation of new neurons. C57BL/6 mice were sensitized with a clinically relevant allergen derived from timothy grass pollen (Phl p 5). As expected, allergic sensitization induced high serum levels of allergen-specific immunoglobulins (IgG1 and IgE) and of TH2 cytokines (IL-5 and IL-13). Surprisingly, fewer Iba1+ microglia were found in the granular layer and subgranular zone of the hippocampal dentate gyrus and also the number of Iba1+MHCII+ cells was lower, indicating a reduced microglial surveillance and activation in the hippocampus of allergic mice. Neurogenesis was analyzed by labeling of proliferating cells with bromodeoxyuridine (BrdU) and determining their fate 4 weeks later, and by quantitative analysis of young immature neurons, i.e. cells expressing doublecortin (DCX). The number of DCX+ cells was clearly increased in the allergy animals. Moreover, there were more BrdU+ cells present in the hippocampus of allergic mice, and these newly born cells had differentiated into neurons as indicated by a higher number of BrdU+NeuN+ cells. In summary, allergy led to a reduced microglia presence and activity and to an elevated level of neurogenesis in the hippocampus. This effect was apparently specific to the hippocampus, as we did not observe these alterations in the subventricular zone/olfactory bulb system, also a region of high cellular plasticity and adult neurogenesis.